2019
DOI: 10.3390/s19143143
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Bridge Fundamental Frequencies Utilizing a Smartphone MEMS Accelerometer

Abstract: Smartphone MEMS (Micro Electrical Mechanical System) accelerometers have relatively low sensitivity and high output noise density. Therefore, it cannot be directly used to track feeble vibrations such as structural vibrations. This article proposes an effective increase in the sensitivity of the smartphone accelerometer utilizing the stochastic resonance (SR) phenomenon. SR is an approach where, counter-intuitively, feeble signals are amplified rather than overwhelmed by the addition of noise. This study intro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…An extended review of SHM applications based on smart sensing units can be found in [56], while [57] discusses the use of such technologies for vehicle-assisted SHM. It is recognized that certain smart technologies (e.g., smartphones and cameras) have been developed for different type of applications and therefore may face certain limitations compared to traditional sensing monitoring units for SHM (e.g., low sensitivity, high input noise in slow acquisition sampling rate from smartphone-embedded accelerometers [58], and low-resolution cameras). Nonetheless, the ever-increasing development of sensor technologies may prove a promising tool for future indirect infrastructural monitoring operations using CAVs.…”
Section: Research Perspectives For Ishm Using Cavsmentioning
confidence: 99%
“…An extended review of SHM applications based on smart sensing units can be found in [56], while [57] discusses the use of such technologies for vehicle-assisted SHM. It is recognized that certain smart technologies (e.g., smartphones and cameras) have been developed for different type of applications and therefore may face certain limitations compared to traditional sensing monitoring units for SHM (e.g., low sensitivity, high input noise in slow acquisition sampling rate from smartphone-embedded accelerometers [58], and low-resolution cameras). Nonetheless, the ever-increasing development of sensor technologies may prove a promising tool for future indirect infrastructural monitoring operations using CAVs.…”
Section: Research Perspectives For Ishm Using Cavsmentioning
confidence: 99%
“…Recently, several studies have compared low-cost MEMS sensors with traditional piezo-electric accelerometers on SHM monitoring tests on real structures. These investigations have shown the technical advantages and limitations of this new digital technology [ 24 , 25 , 26 , 27 , 28 , 29 ]. The MEMS technology has grown quickly in the last few years, new accelerometers being developed with improved properties, accuracy and sensitivity, but keeping their small size, wide variety of available models, and very low cost.…”
Section: Introductionmentioning
confidence: 99%
“…The MEMS technology has grown quickly in the last few years, new accelerometers being developed with improved properties, accuracy and sensitivity, but keeping their small size, wide variety of available models, and very low cost. For that reasons, MEMS accelerometers are suitable for structural monitoring, and many researchers have used this technology to develop new SHM systems [ 23 , 24 , 25 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…1 Investigation of the vibrational response is a typical method which is utilized for structural health monitoring (SHM) over the past decades. 2 Mainly, the extraction of modal parameters is the basis of the judgment relating to structural integrity and safety. [3][4][5] It should be mentioned that these types of SHM methods are less applicable for structures such as tunnels compared to bridges and buildings.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, frequent monitoring of the health of structures is inevitable 1 . Investigation of the vibrational response is a typical method which is utilized for structural health monitoring (SHM) over the past decades 2 . Mainly, the extraction of modal parameters is the basis of the judgment relating to structural integrity and safety 3–5 .…”
Section: Introductionmentioning
confidence: 99%